Assessment of Policy Changes of the Impacts of Urbanization, Economic Growth and Decentralization of Water Services with Regard to Water Quality in Mexico - Lara Cervantes, René Fernando (2016)
The thesis studies the case of water quality in Mexico as a crucial factor to prevent water scarcity. This is an important issue for Mexico since more than half of its territory is arid or semi-arid; moreover, the most productive regions are located in areas with significant water resources stress. In this regard, the current situation of water scarcity is studied from the changes in water management derived from the evolution of institutions in the country. The institutional changes were analyzed mostly in the transition from a centralized water supply and sanitation services with strong state intervention to the decentralization of such services that were transferred to municipalities. Decentralization was addressed by analyzing the performance of water supply and sanitation services in urban areas that are expected to continue growing in the near future. The literature shows that the decentralization process has been partial and has not improved as expected the performance of water supply and sanitation services, moreover, due to political reasons, limited human and financial resources it introduced more challenges to the accomplishment of sustainable water management. More importantly, the federal government is still the main agent for the development of the water sector in Mexico. The next part of the analysis consist of a quantitative and qualitative evaluation regarding water quality for the three most productive Hydrological-Administrative Regions (HARs) of Mexico in the period of 2003-2013. The HARs chosen are the HAR VI Río Bravo, HAR VIII Lerma Santiago Pacific and HAR XIII Waters of the Valley of Mexico which are very similar in terms GDP share and water stress degree. Through OLS regression models for each HAR the impacts of demographic, economic, water supply and sanitation services aspects were tested to known their effects on water quality.